The structure of bacteriophage T7 lysozyme, a zinc amidase and an inhibitor of T7 RNA polymerase. - Cheng, X (1994)
The lysozyme of bacteriophage T7 is a bifunctional protein that cuts amide bonds in the bacterial cell wall and binds to and inhibits transcription by T7 RNA polymerase. The structure of a mutant T7 lysozyme has been determined by x-ray crystallography and refined at 2.2-A resolution. The protein folds into an alpha/beta-sheet structure that has a prominent cleft. A zinc atom is located in the cleft, bound directly to three amino acids and, through a water molecule, to a fourth. Zinc is required for amidase activity but not for inhibition of T7 RNA polymerase. Alignment of the zinc ligands of T7 lysozyme with those of carboxypeptidase A and thermolysin suggests structural similarity among the catalytic sites for the amidase and these zinc proteases. Mutational analysis identified presumed catalytic residues for amidase activity within the cleft and a surface that appears to be the site of binding to T7 RNA polymerase. Binding of T7 RNA polymerase inhibits amidase activity.